ANALISIS PENERAPAN MANAJEMEN RISIKO PADA KESELAMATAN KERJA KARYAWAN PABRIK PENGOLAHAN KELAPA SAWIT DI PT. PASAMAN MARAMA SEJAHTERA - Nisfa Nisfa; Habibatur Ridhah; Zulhelmi Zulhelmi; Novera Martilova (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the implementation of risk management in employee occupational safety at the palm oil processing plant PT. Pasaman Marama Sejahtera. The high potential for occupational accidents in the factory environment is the main background for this study, given its serious impact on the health and safety of workers and the continuity of company operations. This study employs a qualitative field research method, with data collection conducted through interviews, direct observation, and documentation. Data was analyzed using data reduction techniques, data presentation, and conclusion drawing. The results of the study indicate that PT. Pasaman Marama Sejahtera has implemented a risk management system using the HIRARC method (Hazard Identification, Risk Assessment, and Risk Control), which includes hazard identification, risk assessment, and risk control. Although the accident rate over the past three years (2021-2023) has been low and has not resulted in lost work hours, hazard identification reveals potential risks at workstations such as the sterilizer, thresher, pressing, and clarification stations. Risk management is implemented through the use of personal protective equipment (PPE), OSH training, and regular supervision. This study is expected to serve as a reference for companies in improving workplace safety protection and contribute to the literature on OSH risk management in the palm oil processing industry.